2001
DOI: 10.1046/j.1365-2362.2001.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostacyclin by indomethacin ameliorates the splanchnic hyposensitivity to glypressin in haemorrhage‐transfused common bile duct‐ligated rats

Abstract: Prostacyclin (PGI2) is an important contributor to the mediation of hyporeactivity to vasoconstrictors and the development of hyperdynamic circulation in portal hypertensive states. Inhibition of PGI2 synthesis in haemorrhage-transfused partially portal vein-ligated rats could ameliorate the splanchnic hyposensitivity to glypressin, a long-acting vasopressin analogue. This study investigated whether the hyposensitivity to glypressin also exists in rats with common bile duct ligation (BDL) and whether the inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Some studies suggest the possible involvement of other humoral vasodilators, but a definitive pathogenic role for any of these substances remains elusive. This list includes: glucagons [37] , prostaglandins [38] , GABA [39] , VIP [40] , bile acids [41] , endotoxin, histamine [42] and adenosine [43] .…”
Section: Endocannabinoidsmentioning
confidence: 99%
“…Some studies suggest the possible involvement of other humoral vasodilators, but a definitive pathogenic role for any of these substances remains elusive. This list includes: glucagons [37] , prostaglandins [38] , GABA [39] , VIP [40] , bile acids [41] , endotoxin, histamine [42] and adenosine [43] .…”
Section: Endocannabinoidsmentioning
confidence: 99%
“…It is synthesized through cyclooxygenases (COX) including COX-1 and COX-2. The previous studies have reported that COX inhibition attenuated collateral vasodilatation in portal hypertensive and cirrhotic rats [7,8]. In addition, accumulating evidences have identified that COX inhibitors ameliorated acute and chronic liver injury, liver fibrosis and steatosis, abnormal vascular responsiveness, and excessive angiogenesis [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prostacyclin (PGI 2 ) regulates splanchnic blood flow during early haemorrhage/reperfusion injury [11–13] with exaggerated splanchnic PGI 2 release [14]. Furthermore, prostacyclin inhibition ameliorates the splanchnic hyposensitivity to glypressin in haemorrhage‐transfused portal vein‐ligated or bile duct‐ligated rats [15,16]. However, the relative contributions of PGI 2 biosynthesis isoenzymes, cyclooxygenase‐1 (COX‐1) and cyclooxygenase‐2 (COX‐2), in the systemic and splanchnic vasculatures, remain obscure.…”
Section: Introductionmentioning
confidence: 99%